Third‐trimester ultrasound for antenatal diagnosis of placenta accreta spectrum in women with placenta previa: results from the ADoPAD study. (1st September 2022) - Fratelli, N.; Prefumo, F.; Maggi, C.; Cavalli, C.; Sciarrone, A.; Garofalo, A.; Viora, E.; Vergani, P.; Ornaghi, S.; Betti, M.; Vaglio Tessitore, I.; Cavaliere, A. F.; et al.
ABSTRACT: Objective: To evaluate the performance of third‐trimester ultrasound for the diagnosis of clinically significant placenta accreta spectrum disorder (PAS) in women with low‐lying placenta or placenta previa. Methods: This was a prospective multicenter study of pregnant women aged ≥ 18 years who were diagnosed with low‐lying placenta (< 20 mm from the internal cervical os) or placenta previa (covering the internal cervical os) on ultrasound at ≥ 26 + 0 weeks' gestation, between October 2014 and January 2019. Ultrasound suspicion of PAS was raised in the presence of at least one of these signs on grayscale ultrasound: (1) obliteration of the hypoechogenic space between the uterus and the placenta; (2) interruption of the hyperechogenic interface between the uterine serosa and the bladder wall; (3) abnormal placental lacunae. Histopathological examinations were performed according to a predefined protocol, with pathologists blinded to the ultrasound findings. To assess the ability of ultrasound to detect clinically significant PAS, a composite outcome comprising the need for active management at delivery and histopathological confirmation of PAS was considered the reference standard. PAS was considered to be clinically significant if, in addition to histological confirmation, at least one of these procedures was carried out after delivery: use of hemostatic intrauterine balloon, compressive uterine suture, peripartum hysterectomy, uterine/hypogastric artery ligation or uterine artery embolization. The diagnostic performance of each ultrasound sign for clinically significant PAS was evaluated in all women and in the subgroup who had at least one previous Cesarean section and anterior placenta. Post‐test probability was assessed using Fagan nomograms. Results: A total of 568 women underwent transabdominal and transvaginal ultrasound examinations during the study period. Of these, 95 delivered in local hospitals, and placental pathology according to the study protocol was therefore not available. Among the 473 women for whom placental pathology was available, clinically significant PAS was diagnosed in 99 (21%), comprising 36 cases of placenta accreta, 19 of placenta increta and 44 of placenta percreta. The median gestational age at the time of ultrasound assessment was 31.4 (interquartile range, 28.6–34.4) weeks. A normal hypoechogenic space between the uterus and the placenta reduced the post‐test probability of clinically significant PAS from 21% to 5% in women with low‐lying placenta or placenta previa in the third trimester of pregnancy and from 62% to 9% in the subgroup with previous Cesarean section and anterior placenta. The absence of placental lacunae reduced the post‐test probability of clinically significant PAS from 21% to 9% in women with low‐lying placenta or placenta previa in the third trimester of pregnancy and from 62% to 36% in the subgroup with previous Cesarean section and anterior placenta. When abnormal placental lacunae were seen on ultrasound, the post‐test probability of clinically significant PAS increased from 21% to 59% in the whole cohort and from 62% to 78% in the subgroup with previous Cesarean section and anterior placenta. An interrupted hyperechogenic interface between the uterine serosa and bladder wall increased the post‐test probability for clinically significant PAS from 21% to 85% in women with low‐lying placenta or placenta previa and from 62% to 88% in the subgroup with previous Cesarean section and anterior placenta. When all three sonographic markers were present, the post‐test probability for clinically significant PAS increased from 21% to 89% in the whole cohort and from 62% to 92% in the subgroup with previous Cesarean section and anterior placenta. Conclusions: Grayscale ultrasound has good diagnostic performance to identify pregnancies at low risk of PAS in a high‐risk population of women with low‐lying placenta or placenta previa. Ultrasound may be safely used to guide management decisions and concentrate resources on patients with higher risk of clinically significant PAS. © 2022 The Authors. Ultrasound in Obstetrics & Gynecology published by John Wiley & Sons Ltd on behalf of International Society of Ultrasound in Obstetrics and Gynecology. Abstract : This article's abstract has been translated into Spanish and Chinese. Follow the links from the abstract to view the translations. RESUMEN: Ecografía del tercer trimestre para el diagnóstico prenatal del espectro de placenta acreta en mujeres con placenta previa: resultados del estudio ADoPAD Objetivo: Evaluar la eficacia de la ecografía del tercer trimestre para el diagnóstico del trastorno del espectro de la placenta acreta (PAS) clínicamente significativo (PAS, por sus siglas en inglés) en mujeres con placenta baja o placenta previa . Métodos: Este fue un estudio prospectivo multicéntrico de mujeres embarazadas de edad ≥18 años a las que se les diagnosticó con placenta baja (<20mm del orificio cervical interno) o placenta previa (que cubre el orificio cervical interno) en la ecografía de ≥26+0 semanas de gestación, entre octubre de 2014 y enero de 2019. La sospecha ecográfica de PAS se planteó ante la presencia de al menos uno de estos signos en una ecografía en escala de grises: (1) obliteración del espacio hipoecogénico entre el útero y la placenta; (2) interrupción de la interfaz hiperecogénica entre la serosa uterina y la pared vesical; (3) lagunas placentarias anómalas. Los exámenes histopatológicos se realizaron según un protocolo predefinido, en el que los hallazgos ecográficos se ocultaron a los patólogos. Para evaluar la capacidad de la ecografía para detectar el PAS clínicamente significativo, se consideró como estándar de referencia un resultado compuesto que incluía la necesidad de tratamiento activo en el momento del parto y la confirmación histopatológica del PAS. Se consideró que el PAS era clínicamente significativo si, además de la confirmación histológica, se realizó al menos uno de estos procedimientos después del parto: uso de globo intrauterino hemostático, sutura uterina compresiva, histerectomía en el periparto, ligadura de la arteria uterina/hipogástrica o embolización de la arteria uterina. Se evaluó la eficacia para el diagnóstico de cada signo ecográfico para el PAS clínicamente significativo en todas las mujeres y en el subgrupo que tuvo al menos una cesárea previa y placenta anterior. La probabilidad posterior a la prueba se evaluó mediante los nomogramas de Fagan . Resultados: Un total de 568 mujeres se sometieron a ecografías transabdominales y transvaginales durante el periodo de estudio. De ellas, 95 dieron a luz en hospitales locales, por lo que no se dispuso de la patología de la placenta según el protocolo del estudio. Entre las 473 mujeres de las que se disponía de patología placentaria, se diagnosticó PAS clínicamente significativo en 99 (21%), que incluían 36 casos de placenta acreta, 19 de placenta increta y 44 de placenta percreta. La mediana de la edad gestacional en el momento de la evaluación ecográfica fue de 31, 4 (rango intercuartil, 28, 6–34, 4) semanas. Un espacio hipoecogénico normal entre el útero y la placenta redujo la probabilidad posterior a la prueba de PAS clínicamente significativo del 21% al 5% en las mujeres con placenta baja o placenta previa en el tercer trimestre del embarazo y del 62% al 9% en el subgrupo con cesárea previa y placenta anterior. La ausencia de lagunas placentarias redujo la probabilidad posterior a la prueba de PAS clínicamente significativo del 21% al 9% en mujeres con placenta baja o placenta previa en el tercer trimestre del embarazo y del 62% al 36% en el subgrupo con cesárea previa y placenta anterior. Cuando se observaron lagunas placentarias anómalas en la ecografía, la probabilidad posterior a la prueba de PAS clínicamente significativo aumentó del 21% al 59% en toda la cohorte y del 62% al 78% en el subgrupo con cesárea previa y placenta anterior. La interfaz hiperecogénica interrumpida entre la serosa uterina y la pared de la vejiga aumentó la probabilidad posterior a la prueba de un PAS clínicamente significativo del 21% al 85% en mujeres con placenta baja o placenta previa y del 62% al 88% en el subgrupo con cesárea previa y placenta anterior. Cuando los tres marcadores ecográficos estaban presentes, la probabilidad posterior a la prueba de PAS clínicamente significativo aumentó del 21% al 89% en toda la cohorte y del 62% al 92% en el subgrupo con cesárea previa y placenta anterior . Conclusiones: La ecografía en escala de grises tiene una buena eficacia en el diagnóstico para identificar embarazos con bajo riesgo de PAS en una población de alto riesgo de mujeres con placenta baja o placenta previa. La ecografía puede utilizarse con seguridad para guiar las decisiones de tratamiento y concentrar los recursos en las pacientes con mayor riesgo de PAS clínicamente significativo . 摘要: 前置胎盘孕妇的胎盘植入谱系产前诊断的妊娠第三期超声检查:ADoPAD研究结果 目的: 评价妊娠第三期超声检查对低置或前置胎盘孕妇临床上显著的胎盘植入谱系疾病(PAS)的诊断效果。 方法: 本研究属于一项前瞻性多中心研究，研究对象为2014年10月至2019年1月期间，妊娠≥ 26 + 0周时，经超声诊断为低置胎盘(距离宫颈内口小于20毫米)或前置胎盘(覆盖宫颈内口)的孕妇(年龄18周岁或以上)。超声怀疑PAS的条件是灰阶超声至少出现以下一种迹象:(1)子宫和胎盘之间的低回声空间闭塞；(2)子宫浆膜和膀胱壁之间的低回声界面中断；(3)异常胎盘陷窝。根据预先确定的方案进行组织病理学检查，超声检查结果对病理学医师设盲。为了评价超声检查发现临床上显著的PAS的能力，将分娩时需要积极管理和PAS的组织病理学确认在内的综合结果视为参考标准。除了组织病理学确认外，分娩后至少进行以下一种程序，则认为PAS具有临床显著性:使用宫腔止血球囊、子宫压迫缝合术、围产期子宫切除术、子宫/腹下动脉结扎或子宫动脉栓塞术。对所有孕妇以及至少一次剖腹产和前置胎盘的亚组评价每种超声征象对临床上显著的PAS的诊断效果。后验概率使用Fagan列线图进行评价。 结果: 研究期间共计568名孕妇接受经腹部和经阴道超声检查。 其中95名孕妇在本地医院分娩，因此未能遵照研究方案进行胎盘病理检查。在473名提供胎盘病理学资料的孕妇中，99人(21%)被诊断为患有临床显著PAS，包括36例侵入性胎盘、19例植入性胎盘和44例穿透性胎盘。超声评估时的中位胎龄为31.4(四分位数间距，28.6‐34.4)周。子宫和胎盘之间存在正常的低回声空间，因此妊娠第三期低置或前置胎盘孕妇的临床显著PAS后验概率从21%降至5%，而经历过剖腹产和前置胎盘的亚组则从62%降至9%。在无胎盘陷窝的情况下，妊娠第三期低置或前置胎盘孕妇的临床显著PAS后验概率从21%降至9%，而经历过剖腹产和前置胎盘的亚组则从62%降至36%。若超声检查观察到异常胎盘陷窝，整组的临床显著PAS后验概率从21%增加到59%，而经历过剖腹产和前置胎盘的亚组则从62%增加到78%。若发生子宫浆膜和膀胱壁之间的低回声界面中断，低置或前置胎盘孕妇的临床显著PAS后验概率从21%增加到85%，而经历过剖腹产和前置胎盘的亚组则从62%增加到88%。当所有三种超声征象都存在时，整组的临床显著PAS后验概率从21%增加到89%，而经历过剖腹产和前置胎盘的亚组则从62%增加到92%。 结论: 在低置或前置胎盘的高危人群中，灰阶超声对识别低风险PAS的孕妇具有良好的诊断效果。 超声可安全地用于指导管理决策并将资源集中在具有较高临床显著PAS风险的患者身上。